2009
DOI: 10.1089/bfm.2008.0125
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Accurate Test Weighing Technique for Preterm and High-Risk Hospitalized Infants

Abstract: The data from this study support the use of this test weighing technique as an accurate, objective assessment of the measurement of breastmilk intake after a breastfeeding session, thus allowing medical decisions regarding supplementation to be based on objective data rather than inaccurate clinical indices of the quality of infant feedings at the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In clinical practice, objective assessments of breastfeeding often overshadow relational aspects, turning breastfeeding into a productive project (Dykes, 2005). Although test weighing can be regarded as a valid method for assessing milk intake (Haase et al, 2009;Scanlon, Alexander, Serdula, Davis, & Bowman, 2002), maternal confidence and/or maternal competence does not increase with test weighing in hospital or postdischarge (Hall et al, 2002;Hurst et al, 2004), and is thus not a reason for test weighing. However, presentations of alternative methods, where the assessment of milk intake and the support of the maternal/infant developing relationship are accommodated, are lacking in the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, objective assessments of breastfeeding often overshadow relational aspects, turning breastfeeding into a productive project (Dykes, 2005). Although test weighing can be regarded as a valid method for assessing milk intake (Haase et al, 2009;Scanlon, Alexander, Serdula, Davis, & Bowman, 2002), maternal confidence and/or maternal competence does not increase with test weighing in hospital or postdischarge (Hall et al, 2002;Hurst et al, 2004), and is thus not a reason for test weighing. However, presentations of alternative methods, where the assessment of milk intake and the support of the maternal/infant developing relationship are accommodated, are lacking in the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…With this method the infant is weighed before and after each breastfeeding session. Although test weighing is suggested to be a reliable method for assessing intake (Haase, Barreira, Murphy, Mueller, & Rhodes, 2009), it does not appear to be beneficial for maternal role development or mother/infant interaction (Hall, Shearer, Mogan, & Berkowitz, 2002;Hurst, Meier, Engstrom, & Myatt, 2004). The incentives for constructing a new care routine in the NICU were that mothers in Swedish NICUs found test weighing to be "troublesome"; they had to disregard their own and their infants' needs and cues (Flacking, Ewald, Nyqvist, & Starrin, 2006).…”
Section: R E S E a R C Hmentioning
confidence: 99%
“…Multiple studies of test-weights to measure HM intake during breastfeeding reveal that they are accurate, acceptable by mothers, and cannot be replaced by clinical indices such as counting swallows or checking for milk in the infant’s mouth. 45,73,74 One randomized study revealed that mothers of preterm infants can use of test-weights in the home after NICU discharge to manage supplements and complements of their pumped HM until infants can consume exclusive breastfeeds. 75 …”
Section: Feeding At Breast In the Nicumentioning
confidence: 99%
“…In March 2011, a scale was purchased to initiate breastfeeding pre‐ and postweights (test weights). Test weights facilitate transitioning infants to breast feedings by providing an accurate estimate of the volume of HM transferred during a feeding (Haase, Barreira, Murphy, Mueller, & Rhodes (). Although infants initiate nutritive feedings at breast, weighing the infant helps to identify if supplementation is needed.…”
Section: Project Intervention and Implementationmentioning
confidence: 99%